Pelatihan Literasi Bahasa Hukum Sebagai Upaya Pencegahan Kekerasan Verbal dan Perundungan di SMA Negeri 2 Jonggat - Lalu Wirajayadi; Baiq Ishariaty Wika Utary; Fitria Ika Agustina (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Verbal abuse and bullying in school environments remain issues that can compromise student safety, well-being, and psychological development. These forms of abuse range from teasing, insults, threats, and name-calling to social exclusion and the dissemination of demeaning comments via social media. A root cause often overlooked in bullying prevention programs is students' low level of legal literacy; consequently, they fail to distinguish between harmless joking, hurtful speech, and actions that carry legal consequences. This community service initiative aims to enhance the understanding of students at SMA Negeri 2 Jonggat regarding legal terms and concepts related to verbal abuse, bullying, and child protection, while also equipping them with the skills to independently recognize, report, and prevent such actions. The methods employed included participatory legal literacy training, awareness-raising sessions, case simulations, and guidance on establishing an anti-bullying task force within the school. The activities were conducted at SMA Negeri 2 Jonggat, involving 10th and 11th-grade students as primary participants, alongside guidance and counseling teachers. Training materials covered concepts of verbal abuse and bullying, linguistic politeness, students' rights and obligations, child protection, social responsibility, and reporting procedures for bullying incidents. The results indicate an improved student understanding of legal terms related to bullying, increased student confidence in reporting verbal abuse, and the formation of a sustainable student group dedicated to anti-bullying efforts. This program is expected to serve as a replicable model for other schools seeking to prevent verbal abuse and bullying through the strengthening of legal literacy.